2020
DOI: 10.21203/rs.3.rs-27310/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Most frequent South Asian haplotypes of ACE2 share identity by descent with East Eurasian populations

Abstract: It was shown that the human ACE2 is the receptor of recent coronavirus SARS-CoV-2 and variation in this gene may affect the susceptibility of a population. Therefore, we have analysed whole genome data of World populations focusing South Asia. Genetically, South Asians are more related with the West Eurasian populations rather than East Eurasians. Whereas, for this gene, unexpectedly South Asians are more closer to East Eurasians rather than West Eurasians. The phylogenetic analysis suggested that the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

7
1

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
13
3
Order By: Relevance
“…This variant of ACE2 was significantly different for Europeans (0.2), than the East Asians (0.55) ( Asselta et al, 2020 ; Cao et al, 2020 ). Our analysis on Indian population has revealed mean frequency ∼0.6 of this allele ( Srivastava et al, 2020 ). Moreover, our haplotype analysis for this gene revealed excessive sharing of the frequent South Asian haplotypes with East Eurasian populations, rather than West Eurasian populations ( Srivastava et al, 2020 ).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…This variant of ACE2 was significantly different for Europeans (0.2), than the East Asians (0.55) ( Asselta et al, 2020 ; Cao et al, 2020 ). Our analysis on Indian population has revealed mean frequency ∼0.6 of this allele ( Srivastava et al, 2020 ). Moreover, our haplotype analysis for this gene revealed excessive sharing of the frequent South Asian haplotypes with East Eurasian populations, rather than West Eurasian populations ( Srivastava et al, 2020 ).…”
Section: Resultsmentioning
confidence: 70%
“…Our analysis on Indian population has revealed mean frequency ∼0.6 of this allele ( Srivastava et al, 2020 ). Moreover, our haplotype analysis for this gene revealed excessive sharing of the frequent South Asian haplotypes with East Eurasian populations, rather than West Eurasian populations ( Srivastava et al, 2020 ). Similar to the East Asians, we have also noted that the frequency of this allele is significantly higher (two tailed p < 0.0001) among Indian populations in comparison with either of European, American, or African.…”
Section: Resultsmentioning
confidence: 70%
“…The phylogenetic analysis of haplotypes distinctly classifies three types of haplotypes in order to identify the SNP which reveals greater affinity between South Asians and East Eurasians. Out of these three haplotypes-haplotype 3 (ht3) is shown to be harbored by East Eurasians and South Asians and derived from rs2285666 [16]. The ACE2 gene rs2285666 polymorphism is also shown to have association with type 2 diabetes mellitus (T2DM) in which A allele is associated with higher risk of T2DM [17].…”
Section: Ace2 Rs2285666 Association With Spatial Distribution Of Covimentioning
confidence: 99%
“…However, keeping in mind that 1,000 genome South Asian samples do not capture the complete South Asian diversity (36), one should look at these variations as well as whole ACE2 variations in the large number of South Asian ethnic groups. Moreover, the greater role of ACE2 in disease manifestation is evident in our recent study, which showed that the major South Asian ACE2 haplotypes are identity by descent (IBD) of East Eurasians rather than West Eurasian (19), which is possibly one of the reasons for the low mortality among the Indian population. Therefore, studying the detailed ACE2 variations among diverse Indian populations would be worthwhile to understand human susceptibility to Covid-19.…”
mentioning
confidence: 92%
“…Recent research suggests that the coronavirus receptor of human ACE2 plays a pivotal role in disease predisposition, therefore, certain polymorphisms in this gene may affect the susceptibility of a population (14)(15)(16)(17)(18)(19)(20)(21). As an expert on Human Evolutionary Genetics, it is necessary to reiterate that, in India, modern humans have been living for at least 50,000 to 70,000 years and have experienced various kinds of pathogen pressures (22)(23)(24)(25).…”
mentioning
confidence: 99%